Constraints on particles and fields from full Stokes observations of AGN - Daniel C. Homan; Talvikki Hovatta; Yuri Y. Kovalev; Matthew L. Lister; Alexander B. Pushkarev; Tuomas Savolainen (MDPI AG, 2022)
Combined polarization imaging of radio jets from Active Galactic Nuclei (AGN) in circular and linear polarization, also known as full Stokes imaging, has the potential to constrain both the magnetic field structure and particle properties of jets. Although only a small fraction of the emission when detected, typically less than a few tenths of a percent but up to as much as a couple of percent in the strongest resolved sources, circular polarization directly probes the magnetic field and particles within the jet itself and is not expected to be modified by external screens. A key to using full Stokes observations to constrain jet properties is obtaining a better understanding of the emission of circular polarization, including its variability and spectrum. We discuss what we have learned so far from parsec scale monitoring observations in the MOJAVE program and from multi-frequency observations of selected AGN.